Perspectives on the Direction of Cancer Prehabilitation in the Pandemic and Beyond - San San Tay, MBBS, MRCP (UK), MMED (Int Med) (Archives of Rehabilitation Research and Clinical Translation, 2022)
Growing attention has been placed on cancer prehabilitation in the recent years as the number of publications increase. The real-world application of prehabilitation remains heterogeneous and its implementation has been challenging during the COVID-19 pandemic. However, the pandemic has also provided impetus for change-leveraging technology and digitalization. This paper will discuss the pre-existing models of care, adaptations that had taken place in the pandemic, the model of care in the author's institution, and the future direction of cancer prehabilitation.